MeCP2: a critical regulator of chromatin in neurodevelopment and adult brain function - Gülmez Karaca, Kübra; Brito, David V. C.; Oliveira, Ana (International journal of molecular sciences, 2019)
Methyl CpG binding protein 2 (MeCP2) was first identified as a nuclear protein with a transcriptional repressor role that recognizes DNA methylation marks. MeCP2 has a well-established function in neurodevelopment, as evidenced by the severe neurological impairments characteristic of the Rett syndrome (RTT) pathology and the MeCP2 duplication syndrome (MDS), caused by loss or gain of MeCP2 function, respectively. Research aimed at the underlying pathophysiological mechanisms of RTT and MDS has significantly advanced our understanding of MeCP2 functions in the nervous system. It has revealed, however, that MeCP2 has more varied and complex roles than previously thought. Here we review recent insights into the functions of MeCP2 in neurodevelopment and the less explored requirement for MeCP2 in adult brain function. We focus on the emerging view that MeCP2 is a global chromatin organizer. Finally, we discuss how the individual functions of MeCP2 in neurodevelopment and adulthood are linked to its role as a chromatin regulator.
Gesehen am 06.12.2019